ANALISIS PENGARUH PENDAPATAN ASLI DAERAH, DANA BAGI HASIL, JUMLAH PENDUDUK TERHADAP BELANJA DAERAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Resti Januarti; Susi Wulandari; Silva Prasasti; Ferdi Yanto; Saiful Anwar (JURNAL CAFETARIA, 2022)
The purpose of this study was to examine the effect of local revenue, revenue-sharing, and population on district/municipal expenditures in Central Java Province. The samples used were 8 districts/cities which were selected by purposive sampling. The data used is secondary data obtained from BPK and BPS. The analytical method used is multiple linear regression. The results of the study partially show that the regional original income variable has a significant effect on regional expenditure. Then the profit-sharing variable has no significant effect on regional expenditure. Finally, the population has a significant effect on regional expenditure. It is hoped that this research can be a reference for local governments to utilize existing resources, as well as optimize local revenue and revenue-sharing funds, so as to improve community welfare.